The gendered nature of careers: Evidence from a Malaysian university - Ismail, Maimunah (Journal of International Management Studie, 2009)
Career is an area through which its interaction with gender explains the dynamism between men, women, workand organizations. It is argued that career is gendered i.e. it goes according to marked divisions of men and women. However, the question of the gendered nature of career is still less understood. This article aims to highlight emerging concepts and realities about the gendered nature of careers. The paper first theorizes gender and careers, presentssome data on demography, employment and career positions by gender in Malaysia and in a selected university in the country. The paper then highlights the implications of the gendered nature of careers to individuals and the institution; and finally draws conclusions and identifies challenges in terms of policy development in higher education. Keywords: Career, gender, career development